PATERNAL ABSENCE AND IDEOLOGICAL TRANSITION: ANALYZING THE VANISHING MEDIATOR IN ORHAN PAMUK'S THE RED-HAIRED WOMAN (International Journal of Food and Nutritional Sciences, 2022)
The main theme of the fiction written by Orhan Pamuk is always the crisis of the modern Turkish subject that finds itself in an impossible contradiction between the Eastern tradition and the secular modernization of the West. This paper discusses the character change of Cem in The Red-Haired Woman by contending that his turn into an idealistic, leftist young man to a rich capitalist man is a dialectically necessary reaction to the trauma of relationships. The analysis utilizes the concept of Vanishing Mediator (VM) and Oedipal Guilt Complex developed by Jameson/Zizek. Master Mahmut, the well-digger, serves as the VM: he delivers the utilitarian ethics of bringing in the new ideology of secular capitalism, and has to then figuratively or literally vanish. The guilt complex thus created out of Oedipal structure is construed as the fundamental psychological process that drives Cem to the materialistic path. According to this reading, the required, but tragic, historical change towards a new capitalist reality is justified, as it is personal pain framed as the structural necessity of ideological processing.